2001
DOI: 10.1097/00005344-200104000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation Therapy on Vascular Responsiveness

Abstract: The use of radiation therapy to inhibit vascular proliferative diseases has produced encouraging results in several clinical trials. However, little is known about the possible side effects of radiation on vascular responsiveness. Our goal was to study the in vitro vascular responses of the rabbit aorta to various agonists immediately after several regimens of radiation therapy administered at doses prescribed in clinical protocols and at two different dose rates. High-dose-rate radiation was administered eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The absence of effect of preoperative radiotherapy on the in vitro relaxation to sildenafil may be due to its direct mechanism of action on muscle PDE5, which is unrelated to neural release of mediators. A similar lack of influence of clinical doses of radiation has been reported for directly contracting and relaxing agents in isolated vascular smooth muscle29.…”
Section: Discussionsupporting
confidence: 72%
“…The absence of effect of preoperative radiotherapy on the in vitro relaxation to sildenafil may be due to its direct mechanism of action on muscle PDE5, which is unrelated to neural release of mediators. A similar lack of influence of clinical doses of radiation has been reported for directly contracting and relaxing agents in isolated vascular smooth muscle29.…”
Section: Discussionsupporting
confidence: 72%
“…In contrast to the numerous studies demonstrating that irradiation depresses endothelium-dependent vasorelaxation, other investigations have shown that irradiation enhances vascular contractility in an endothelium-independent manner (20,39). This information suggests that, in addition to the indirect effect through a decrease in endothelial-dependent relaxation, a direct effect on vascular contractility may be important in the vascular anomalies induced by irradiation.…”
mentioning
confidence: 76%
“…Whole body irradiation with a dose of 2 Gy enhanced immediate B1 receptor expression in the heart (28). Ex vivo beta and gamma irradiation of rabbit aorta induced B1 gene expression within hours after irradiation, and the response to B1 activation was enhanced (29). To our knowledge, this is the first study to examine left ventricular expression of bradykinin receptors several months after irradiation.…”
Section: Discussionmentioning
confidence: 99%